2009
DOI: 10.1016/j.febslet.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

FKBP25, a novel regulator of the p53 pathway, induces the degradation of MDM2 and activation of p53

Abstract: Edited by Angel NebredaKeywords: FKBP25 MDM2 p53 E3 ligase Ubiquitylation Degradation a b s t r a c tThe p53 tumour suppressor protein is tightly controlled by the E3 ubiquitin ligase, mouse double minute 2 (MDM2), but maintains MDM2 expression as part of a negative feedback loop. We have identified the immunophilin, 25 kDa FK506-binding protein (FKBP25), previously shown to be regulated by p53-mediated repression, as an MDM2-interacting partner. We show that FKBP25 stimulates auto-ubiquitylation and proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 15 publications
2
51
1
Order By: Relevance
“…The remaining chromatin-associated interactions identified by in-solution digestion will be described in a separate publication. This link is notable in light of previous findings that FKBP25 regulates p53 levels via MDM2 (Ochocka et al 2009), and KAP1, PARP1, and RPA1 all have links to the regulation of p53 in DNA damage (Valenzuela et al 2002;Bochkareva et al 2005;Wang et al 2005). In support of a potential role for FKBP25 in chromatin biology, histone deacetylaces (HDAC) 1 and 2 have been identified as FKBP25-associated proteins (Yang et al 2001), and Mybbp1a and KAP1 are found in complexes containing HDAC1 and 2 (Schultz et al 2001;Tan et al 2012).…”
Section: Fkbp25 Localizes To the Nucleus And Nucleolus And Associatesmentioning
confidence: 66%
See 3 more Smart Citations
“…The remaining chromatin-associated interactions identified by in-solution digestion will be described in a separate publication. This link is notable in light of previous findings that FKBP25 regulates p53 levels via MDM2 (Ochocka et al 2009), and KAP1, PARP1, and RPA1 all have links to the regulation of p53 in DNA damage (Valenzuela et al 2002;Bochkareva et al 2005;Wang et al 2005). In support of a potential role for FKBP25 in chromatin biology, histone deacetylaces (HDAC) 1 and 2 have been identified as FKBP25-associated proteins (Yang et al 2001), and Mybbp1a and KAP1 are found in complexes containing HDAC1 and 2 (Schultz et al 2001;Tan et al 2012).…”
Section: Fkbp25 Localizes To the Nucleus And Nucleolus And Associatesmentioning
confidence: 66%
“…S2). In support of this, FKBP25 has an exposed nuclear localization signal (NLS), accumulates in the nucleus upon treatment with the nuclear export inhibitor Leptomycin B (LMB) (Ochocka et al 2009), and its reported functions are carried out in the nucleus. Additionally, we performed chromatin immunoprecipitation (ChIP) using antisera raised against the N terminus of FKBP25.…”
Section: Fkbp25 Localizes To the Nucleus And Nucleolus And Associatesmentioning
confidence: 93%
See 2 more Smart Citations
“…[3][4][5][6] Human FKBP25 is a 25 kDa protein which bears two domains linked by a long flexible loop. 7 Its C-terminal domain contains the well-conserved FK506 or rapamycin binding pocket, hence termed as the FK506 binding domain (FKBD).…”
Section: Introductionmentioning
confidence: 99%